Static and dynamic buckling of thin-walled plate structures - Kubiak, Tomasz (Springer International Publishing, 2013)
This monograph deals with buckling and postbuckling behavior of thin plates and thin-walled structures with flat wall subjected to static and dynamic load. The investigations are carried out in elastic range. The basic assumption here is the  thin plate theory. This method is used to determination the buckling load and postbuckling analysis of thin-walled structures subjected to static and dynamic load. The book introduces two methods for static and dynamic buckling investigation which allow for a wider understanding of the phenomenon. Two different methods also can allow uncoupling of the phenomena occurring at the same time and attempt to estimate their impact on the final result. A general mathematical model, adopted in proposed analytical-numerical method, enables the consideration of all types of stability loss i.e.local, global and interactive forms of buckling. The applied numerical-numerical method includes adjacent of walls, shear-lag phenomenon and a deplanation of cross-sections.